The imperfect nutritionist : 7 principles of healthy eating - Medhurst, Jennifer (London : Kyle Books, an imprint of Octopus Publishing Group Limited, 2023)
"Backed by science, The Imperfect Nutritionist celebrates food first, rather than looking at it as points on a plate. Instead of adopting a one-size-fits-all approach and telling the reader what they can and cannot eat, it acknowledges the complexities and uniqueness of the body and offers a diet that you can tailor to your own individual needs. Part One outlines seven general principles that Jennifer believes underpins any healthy diet: eat whole, be diverse, factor in fats, include fermented foods, reduce refined carbohydrates, know your liquids, eat mindfully. Part Two consists of a 2-week plan plus 100 recipes of dishes that you actually want to cook and eat, using ingredients available at any supermarket"--
Ingredient list -- 2-week plan -- Principles. 1. Focus on whole foods -- 2. Be diverse -- 3. What the fat!? -- 4. Include fermented, prebiotic & probiotic foods -- 5. Reduce refined carbohydrate -- 6. Be aware of liquids -- 7. Eat mindfully -- Recipes. Breakfast & brunch -- Soups, salads & sandwiches -- Mains -- Desserts & sweet things -- Drinks.
Includes index.
Includes index.
Keywords: Cooking; Nutrition; Health -- Nutritional aspects; Cookbooks